(untitled) (Revista Educação, Artes e Inclusão, 2025)
This study presents a case report of a special school student with difficulties in carrying out pedagogical activities. This work aims to improve the student’s locomotion, providing autonomy of locomotion and independence to carry out activities. This is an excerpt from a descriptive doctoral study with a qualitative approach. The instruments used were the WHOQOL-100 questionnaire before and after using the automated wheelchair, observations described in a diary and the Visual Analog Satisfaction Scale. The student used the chair for 15 days, with virtual use orientation sessions. Through the results found in the pre- and post-use of the chair, there was an improvement in the perception of the student’s quality of life in facets related to levels of independence and social relationships. The reports presented corroborate the results filled in on the satisfaction scale, proving the benefits caused at home for locomotion, communication and interaction with family members. It is concluded that the development of assistive technologies capable of meeting the specific needs of each person with a disability requires time, many studies and follow-up so that the potential for safely promoting benefits can be evaluated.